Physical, digital, virtual, intangible. Research experiences in Museums - Massimiliano Lo Turco; Elisabetta Caterina Giovannini; Andrea Tomalini (Agathón)
This paper dwells on the many meanings the digital artefacts can have, their value and their replicability. It presents some critical and methodological thoughts on the use of digital tools in the museums. Using consolidated taxonomies and redefining the digital tools to be innovatively applied to Cultural Assets, the essay describes some research experiences carried out over the last years. From the creation of virtual reconstructions of the past, to the opportunity to work on virtual models, operating on informative stratification not perceptible by simply observing the collection’s item and avoiding its evolution into a simple repetition of the perceptual experience of the real object.